Some principles and issues in implementing agricultural research networks - Kirkby, Roger A. (International Center for Tropical Agriculture, 1987)
The operating principles involved in implementing agricultural research networks, with special reference to the African bean research network, are reviewed. Issues briefly discussed are (1) the need for more precise definition of intended participation for each network activity; (2) less overburdening of national research capacity; (3) increased flexibility in form and extent of participation to close the gap between larger, stronger National Agricultural Research Systems (NARS) and smaller, less developed ones; (4) increased participation in decision-making within the network; and (5) cooperation between networks since scientists or national programs may belong to more than one network. The sustainability of research networks is posed as the most crucial issue; the commitment of NARS to long-term existence of the networks and their future form and function is therefore emphasized. This issue will greatly influence the future role of international organizations as long-term coordinators or as liason with native networks to ensure access to results of upstream research. (CIAT)